(untitled) (CIPEEX, 2026)
Introduction: Leprosy is a chronic disease caused by Mycobacterium leprae. Brazil ranks second worldwide in absolute cases and is classified by the WHO as a high-burden country, requiring epidemiological monitoring to guide elimination strategies. Objective: To analyze the temporal trend and spatial distribution of leprosy in the Southeast region of Brazil from 2013 to 2023, and to identify vulnerable groups. Method: Ecological, retrospective, and analytical study using DATASUS/TabNet data for Southeast states. Absolute and relative frequencies, CAGR, and spatial distribution (choropleth maps) were analyzed, and sociodemographic profiles described. Results: A total of 51,077 cases were reported. A decline was observed until 2019, followed by a sharp drop in 2020, with subsequent recovery not reaching previous levels. CAGR indicated an average annual decrease of -2.97%. São Paulo had the highest absolute number (17,801), while Espírito Santo showed the highest proportional rate (162.7/100,000). Most cases occurred in males (55.9%), adults aged 20–59 years (63.9%), and elderly individuals (29.4%). Incomplete primary education predominated (39.1%), and Black and Brown populations were most affected (53.1%). Conclusion: The Southeast region showed an overall decline in leprosy, although unevenly distributed. Higher risks persist among men, adults, the elderly, individuals with low education, and Black and Brown populations. These findings highlight the need for targeted strategies to reduce inequalities and advance towards the WHO goal of leprosy elimination.